Perbandingan Struktur dan Perilaku Pasar Persaingan Monopolistik dan Oligopoli dalam Perspektif Ekonomi Mikro - Shinta Jouito Samosir; Virma Dinartha Sinaga; Siti Rahma Fadillah; Yohana Tio Syarina Siringoringo; Evi Syuriani Harahap (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study examines a comparison between the structure of monopolistic competition and oligopoly markets in microeconomics. Market structure determines competition, price formation, production levels, as well as efficiency and consumer welfare. A qualitative approach using library research is employed, reviewing relevant scientific literature and journals. The analysis results show that monopolistic competition markets have many players with differentiated products and low entry barriers. Competition is more focused on non-price strategies such as innovation, promotion, and brand image. In the long run, economic profits decrease to normal profits due to the ease of market entry, despite the existence of excess capacity. Meanwhile, the oligopoly market has few firms with high interdependence in strategic decision-making, influenced by the anticipation of competitors’ reactions. Game theory models such as Cournot, Bertrand, and Stackelberg are relevant to explain the dynamics of competition. The oligopoly structure has high entry barriers and the potential for collusion, which can affect prices and consumer welfare. The comparison shows that monopolistic competition markets excel in product diversity and ease of entry, while oligopoly markets can achieve large economies of scale and drive innovation, but pose risks for anti-competitive practices. Understanding these two market structures is essential for policymakers, academics, and business practitioners.